A Comparative Spatiotemporal Analysis for Long-Term Trends of Hydrometeorological Variables in Maritsa River Basin - Mehmet Seren Korkmaz; Kevser Merkür Başkesen; Ertuğrul Sunan (Doğal Afetler ve Çevre Dergisi)
Revealing long-term trends in hydrometeorological variables plays a critical role in the sustainable management and planning of water resources. These analyses are necessary to understand climate change impacts, taking precautions for natural disasters, plan agricultural activities, and develop water management strategies. The aim of this study is to examine the changes in monthly and annual total precipitation and evapotranspiration values in the Maritsa River Basin, a transboundary water basin between Bulgaria, Greece, and Türkiye. For this, precipitation values for the 1982-2023 water years were taken from the Climate Hazards Group InfraRed Precipitation with Stations (CHIRPS) data set, and evapotranspiration values for the 1982-2023 water years were taken from the European Reanalysis 5th Generation-Land (ERA5-Land) data set. The Mann-Kendall, Sen's slope estimator, and Innovative Trend Analysis (ITA) methods were used to determine trends. According to the test results, there is a statistically significant increase in annual total precipitation values within the 95% confidence interval and in annual total evapotranspiration values within the 99% confidence interval. Specifically with all three methods positive and statistically significant trends are observed in precipitation in October, January, May and June. In the monthly evapotranspiration trend analysis, a statistically significant increase is observed except for November, December, June and July. Trend increases were visualized using the graphical method ITA. Significant increasing trends in both monthly and annual precipitation and evapotranspiration reveal changes in the hydrological cycle of the basin. The test results can be used in planning and solving problems related to the basin area.